Excellent Stability of Perovskite Solar Cells Encapsulated With Paraffin/Ethylene-Vinyl Acetate/Paraffin Composite Layer - Long, Biyu; Zhou, Xianzi; Cao, Huafeng; Chen, Renjie; He, Nannan; Chi, Lina; Fan, Penghui; Chen, Xiaohong (Frontiers in Materials, 2022)
The superior encapsulation technology is important for PSCs to prolong its lifetime and realize its commercial application. The Paraffin/EVA/Paraffin composite encapsulated layers were fabricated with the ambient environment under the thermal temperature of 80°C, which have advantages for simple procedures and low cost. PSCs encapsulated with Paraffin/EVA/Paraffin and pure EVA layers maintained 95% and 45% of the initial power conversion efficiency (PCE) aged for 1000h at RH 75%, respectively. Paraffin/EVA/Paraffin-encapsulated PSCs were immersed in water for 5h, which remained 98% of the original PCE, which is far superior to EVA-encapsulated PSCs. The paraffin of high melting point with 68°C show better encapsulation compared to low melting point (60°C and 55℃) paraffins, indicating that high molecular weight of paraffin helps to improve encapsulation performance of PSCs. PSCs encapsulated with Paraffin/EVA/Paraffin showed better stability of Voc compared to pure EVA layer because Paraffin can inhibit defects, voids and edges of metal electrodes quickly expand and decay. Therefore, Paraffin/EVA/Paraffin combination encapsulation is an effective strategy, which can form continuous and dense hydrophobic composite encapsulation films with friendly metal electrode.